Vitamin B12 status in health and disease: a critical review. Diagnosis of deficiency and insufficiency – clinical and laboratory pitfalls. (18th August 2021) - Sobczyńska-Malefora, Agata; Delvin, Edgard; McCaddon, Andrew; Ahmadi, Kourosh R.; Harrington, Dominic J.
Abstract: Vitamin B12 (cobalamin) is an essential cofactor for two metabolic pathways. It is obtained principally from food of animal origin. Cobalamin becomes bioavailable through a series of steps pertaining to its release from dietary protein, intrinsic factor-mediated absorption, haptocorrin or transcobalamin-mediated transport, cellular uptake, and two enzymatic conversions ( via methionine synthase and methylmalonyl-CoA-mutase) into cofactor forms: methylcobalamin and adenosylcobalamin. Vitamin B12 deficiency can masquerade as a multitude of illnesses, presenting different perspectives from the point of view of the hematologist, neurologist, gastroenterologist, general physician, or dietician. Increased physician vigilance and heightened patient awareness often account for its early presentation, and testing sometimes occurs during a phase of vitamin B12 insufficiency before the main onset of the disease. The chosen test often depends on its availability rather than on the diagnostic performance and sensitivity to irrelevant factors interfering with vitamin B12 markers. Although serum B12 is still the most commonly used and widely available test, diagnostics by holotranscobalamin, serum methylmalonic acid, and plasma homocysteine measurements have grown in the last several years in routine practice. The lack of a robust absorption test, coupled with compromised sensitivity and specificity of other tests (intrinsic factor and gastric parietal cell antibodies), hinders determination of the cause for depleted B12 status. This can lead to incorrect supplementation regimes and uncertainty regarding later treatment. This review discusses currently available knowledge on vitamin B12, informs the reader about the pitfalls of tests for assessing its deficiency, reviews B12 status in various populations at different disease stages, and provides recommendations for interpretation, treatment, and associated risks. Future directions for diagnostics of B12 status and health interventions are also discussed.